The roles of short and long chain fatty acids on physicochemical properties and improved cancer targeting of albumin-based fattigation-platform nanoparticles containing doxorubicin - Park, Chulhun; Meghani, Nileshkumar; Amin, Hardik; Tran, Phuong H.L.; Tran, Thao T.D.; Nguyen, Van H.; Lee, Beom Jin (International Journal of Pharmaceutics, 2019)
The aim of this study was to investigate the impact of different chain length fatty acids on physicochemical properties and cancer targeting of fattigation-platform nanoparticles (NPs). Two different types of fatty acids (short chain, 2-hydroxybutyric acid, C4; long chain, oleic acid, C18:1) were successfully conjugated to human serum albumin (HSA) via simple 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) coupling reaction. These conjugates readily formed HSA-C4 and HSA-C18:1 NPs which showed good stability in serum and desirable biocompatibility with normal cell line (HEK293T). Doxorubicin hydrochloride (DOX) was efficiently loaded into NPs by incubation process via electrostatic interaction. The structure, morphology, and texture of DOX-loaded NPs were characterized by Transmission electron microscopy (TEM) equipped with Energy-dispersive X-ray spectroscopy (EDS). The initial burst release of DOX-loaded NPs was controlled by the presence and chain length of fatty acids. In vitro cytotoxicity studies with three cancer cell lines (A549, HT-29, and PANC-1) suggested that fattigation-platform NPs have distinctive cytotoxic effects compared to Doxil ® . Confocal microscopy and flow cytometry exhibited that the cellular uptake of DOX-loaded NPs was varied by the different chain lengths of fatty acids. It was evident that the chain length of fatty acids in the fattigation-platform NPs could play a vital role in varying physicochemical properties and cancer cell targeting of NPs.
Keywords: Antibiotics, Antineoplastic; Cell Line, Tumor; Cell Survival; Doxorubicin; Drug Liberation; HEK293 Cells; Humans; Hydroxybutyrates; Nanoparticles; Neoplasms; Oleic Acid; Serum Albumin, Human; Cancer cell targeting; Different chain length fatty acids; Doxorubicin hydrochloride; Drug loading method; Fattigation-platform; Physicochemical properties; Self-assembled albumin nanoparticle